Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1063/1.4959897
|View full text |Cite
|
Sign up to set email alerts
|

Growth of monolithic full-color GaN-based LED with intermediate carrier blocking layers

Abstract: Specially designed intermediate carrier blocking layers (ICBLs) in multi-active regions of III-nitride LEDs were shown to be effective in controlling the carrier injection distribution across the active regions. In principle, the majority of carriers, both holes and electrons, can be guided into targeted quantum wells and recombine to generate light of specific wavelengths at controlled current-densities. Accordingly we proposed and demonstrated a novel monolithic InGaN-based LED to achieve three primary color… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 14 publications
0
34
0
Order By: Relevance
“…Indium Gallium Nitride is a successful material for the realization of efficient short-wavelength commercial light emitting diodes (LEDs) [1][2][3]. As a matter of fact, InGaN potentially covers the whole visible spectrum, thus allowing in principle to eliminate the phosphor based down conversion and enabling a color mixing approach, which would allow to further increase overall white LED efficiency [4].…”
Section: Introductionmentioning
confidence: 99%
“…Indium Gallium Nitride is a successful material for the realization of efficient short-wavelength commercial light emitting diodes (LEDs) [1][2][3]. As a matter of fact, InGaN potentially covers the whole visible spectrum, thus allowing in principle to eliminate the phosphor based down conversion and enabling a color mixing approach, which would allow to further increase overall white LED efficiency [4].…”
Section: Introductionmentioning
confidence: 99%
“…Most natural IBL design applications, however, include structures which essentially require the injection distribution control over MQW active regions with only few QWs, such as monolithic tunable multi-color LEDs. Color control ability of IBL the active region has been demonstrated in the full red-green-blue (RGB) spectrum [11] and recently also used in a white-color LED with a tunable color temperature [13]. Figure 5 presents an example of chromaticity characteristics' control in the three-color IBL LED of the current design.…”
Section: Resultsmentioning
confidence: 95%
“…The optimal IBL layout would also essentially depend on the required LED operational conditions like nominal bias voltage or injection current. This approach has been successfully applied to achieve the first full-color tunable monolithic LED covering complete RGB gamut [11,12], and recently, has been used to implement a white-color LED with tunable color temperature [13]. In this paper, we demonstrate yet another example of the IBL design of III-nitride MQW LED active region featuring a uniform population of active quantum wells at LED operational voltage.…”
Section: Introductionmentioning
confidence: 99%
“…However, because the driving circuit for this structure is too complicated to realize the independent control of each pixel, this technology is currently unable to achieve a full-color micro-LED display, and the IQE and color adjustment range of the device needs to be further optimized. In 2016, Chen’s team inserted a carrier blocking layer (ICBL) between multiple QWs in different active regions [ 107 ]. The experiments showed that ICBL can guide most of the carriers (holes and electrons) into the target QW where they recombine, thereby generating light of a specific wavelength under the injection of different controlled currents.…”
Section: Monolithic Multi-color Growth Technologymentioning
confidence: 99%